A DESAIN SMART ARMY ROBOT SEBAGAI MEDIA PEMANTAU DAN NEGOSIASI BERBASIS ARTIFICIAL INTELLIGENCE: DESAIN SMART ARMY ROBOT SEBAGAI MEDIA PEMANTAU - tadianta m., Winardi aries; Widiatmoko, Dekki; Hairani, Hairani (Pustaka Poltekad, 2024)
One of the most critical components of hostage rescue efforts is the agreement on hostage release. Officer errors in taking action during the negotiation process can jeopardize the safety of personnel and officers as well as hostage victims. Lack of communication often leads to dangerous conflicts that can hamper hostage taking. To solve this problem, we designed a specialized negotiation robot that is armed to ensure the safety and security of officers in the line of duty, both in war situations and hostage release operations. By having weapons, officers responsible for the safety of victims can perform their duties without compromising their personal security. These military robots enable negotiation and monitoring without threatening lives, providing a more efficient and safe approach. In addition, the robot's ability to operate autonomously with the help of artificial intelligence allows for faster assessment of the situation and a more appropriate response, thereby increasing the chances of a successful rescue mission without adding risk to the humans involved. The robot is also equipped with advanced sensors and machine learning algorithms that can detect changes in the hostage-taker's behavior and body language, providing valuable information to the negotiation team to devise a more effective strategy. Thus, the implementation of this technology not only improves the security and efficiency of military operations, but also paves the way for further innovations in the use of robotics and Artificial Intelligence in various aspects of defense and security.